Telementoring in education of laparoscopic surgeons: An emerging technology - Bogen, Etai M (Baishideng Publishing Group Inc, 2014)
Laparoscopy, minimally invasive and minimal access surgery with more surgeons performing these advanced procedures. We highlight in the review several key emerging technologies such as the telementoring and virtual reality simulators, that provide a solid ground for delivering surgical education to rural area and allow young surgeons a safety net and confidence while operating on a newly learned technique.